Analysis Of Financial Report Fraud Through The Pentagon Fraud Approach - Nadya Andreyanto; Selma Nevira Shinta Putri; Hwihanus Hwihanus (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The purpose of the meta-analysis in this study is to explain and prove the relationship between Pentagon Fraud and Financial Report Fraud. The articles used in this meta-analysis were collected through electronic journals. There are five journals that can be studied qualitatively. The results show that previous research studies concluded that pressure and opportunities cause fraud in financial reports. Researchers found a weakness in previous research: the pressure variable focused too much on financial targets. So few people pay attention to external pressure.